2010
DOI: 10.1038/onc.2010.458
|View full text |Cite
|
Sign up to set email alerts
|

A positive feedback loop of ER-α36/EGFR promotes malignant growth of ER-negative breast cancer cells

Abstract: It is prevailingly thought that estrogen signaling is not involved in development of estrogen receptor (ER)-negative breast cancer. However, there is evidence indicating that ovariectomy prevents the development of both ER-positive and -negative breast cancer, suggesting that estrogen signaling is involved in the development of ER-negative breast cancer. Previously, our laboratory cloned a variant of ER-α, ER-α36, and found that ER-α36 mediated non-genomic estrogen signaling and is highly expressed in ER-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
181
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(198 citation statements)
references
References 23 publications
15
181
0
2
Order By: Relevance
“…Yingchun Zhao, 1 Caishu Deng, 2 Weida Lu, 1 Jing Xiao, 1 Danjun Ma, 1 Mingxi Guo, 1 Robert R Recker, ER-α36 expression was detected in both ER-α66-positive and-negative breast cancer tumors (10,11). High levels of ER-α36 expression also are associated with tamoxifen resistance; breast cancer patients with tumors highly expressing ER-α36 benefit less from tamoxifen treatment (12).…”
Section: O L M E D 1 7 ( 1 1 -1 2 ) 1 2 3 3 -1 2 4 1 N O V E M B mentioning
confidence: 99%
“…Yingchun Zhao, 1 Caishu Deng, 2 Weida Lu, 1 Jing Xiao, 1 Danjun Ma, 1 Mingxi Guo, 1 Robert R Recker, ER-α36 expression was detected in both ER-α66-positive and-negative breast cancer tumors (10,11). High levels of ER-α36 expression also are associated with tamoxifen resistance; breast cancer patients with tumors highly expressing ER-α36 benefit less from tamoxifen treatment (12).…”
Section: O L M E D 1 7 ( 1 1 -1 2 ) 1 2 3 3 -1 2 4 1 N O V E M B mentioning
confidence: 99%
“…ER-α36 mediated mitogenic estrogen signaling in ER-negative breast cancer cells, such as MDA-MB-231 and MDA-MB-436 cells that lack expression of ER-α66 but highly express ER-α36. It was reported that E 2 β induced the MAPK/ERK activation through a mechanism that involves ER-α36 and the EGFR/Src/Shc complex and exhibited a potent mitogenic estrogen signaling in vitro and in vivo [11,12,14]. …”
Section: Discussionmentioning
confidence: 99%
“…ERα-36 was expressed in ER-negative tumor samples and ER-negative breast cancer cell lines [14]. Some studies have suggested that ERα-36 is involved in nongenomic estrogen signaling, and ERα-36 promotes cell proliferation via the MAPK/ERK pathway in ER-negative breast cancers [13,14]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study depicts a novel cross-talk mechanism in which Advances in Breast Cancer Research EGFR and ERα36 positively regulate each other in TNBC, however ERα36 may dynamically change its partners during estrogen signaling in regards to EGFR and Src/Shc [163]. A mechanism for GPER has also been speculated.…”
Section: Localization Of Estrogen Receptor Is Significant In Breast Cmentioning
confidence: 99%